Preparation and characterization of physical properties of molded pulp from empty fruit bunches of oil palm - LUBIS, ROSLIANA; RIYANTO, RIYANTO; SAISA, SAISA (Jurnal Natural, 2024)
This research aims to determine the impact of pretreatment on empty fruit bunches (EFB) of palm oil fibers before the pulping process on the quality of the molded pulp produced. The study includes EFB fiber pretreatment processes, pulp production, pulp molding, physical characteristic analysis, and molded pulp performance evaluation. The pulp production process involves acid-base hydrolysis reactions. The produced molded pulp is done manually. Characterization of the molded pulp includes measurements of paper grammage, thickness, density, and moisture content. The characteristics of pulp produced from pretreated EFB fibers are as follows: an average grammage value of 415.48 g/m, paper thickness of 1.53 mm, water absorption capacity of 13.33-33.33%, density of paper of 0,026 x 106 - 0,027 x 106 g/m3, and a smooth surface morphology. Meanwhile, the characteristics of pulp produced from without pretreatment EFB fibers include an average grammage value of 372.18 g/m, paper thickness of 0.77 mm, water absorption capacity of 20.34-43.21%, density of paper of 0,004 x 106 - 0,008 x 106 g/m3, and a rough surface morphology due to pores on the fiber surface.